1984
DOI: 10.1136/bmj.288.6418.678
|View full text |Cite
|
Sign up to set email alerts
|

Relation between osmolality of diet and gastrointestinal side effects in enteral nutrition.

Abstract: the protein bound cobalamin absorption test takes into account the release of cobalamin from protein as well. By doing so it probably shows an earlier and lesser degree of gastric atrophy than that found in pernicious anaemia that is nevertheless sufficient to lead to cobalamin deficiency. Relation between osmolality of diet and gastrointestinal side effects in enteral nutrition P P KEOHANE, HELEN ATTRILL, MARY LOVE, P FROST, D B A SILK Abstract One hundred and eighteen patients with normal gastrointestinal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(48 citation statements)
references
References 7 publications
0
46
0
2
Order By: Relevance
“…Significantly more treatment patients received enteral feeding formula with osmolality >500 mOsm/kg, usually to restrict fluid input. Although it has been suggested that the hyperosmolar formula does not contribute to diarrhea in patients with normal gastrointestinal functioning, 50 it is possible that it could make a difference in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly more treatment patients received enteral feeding formula with osmolality >500 mOsm/kg, usually to restrict fluid input. Although it has been suggested that the hyperosmolar formula does not contribute to diarrhea in patients with normal gastrointestinal functioning, 50 it is possible that it could make a difference in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…'6 Traditional starter regimens may prevent satisfaction of nutritional demands over the first three to four days of feeding.35 36 Controlled data now available have cast doubt on this practice, there being no difference in the incidence of diarrhoea between a hypotonic starter regimen, an isotonic regimen, and an undiluted hypertonic polymeric diet given by gravity assisted continuous infusion. 35 The final volume of feed required will depend on its energy and nitrogen density, which in turn must be based on water requirements (or restrictions) and nutritional needs.…”
Section: Bolus or Continuous Infusion?mentioning
confidence: 99%
“…There is an undisputed association between enteral feeding, antibiotics and diarrhoea Keohane et al 1983Keohane et al , 1984Bastow, 1986;Guenter et al 1990). The incidence of diarrhoea in enterally-fed patients taking antibiotics far exceeds the incidence in normally-fed patients taking the same antibiotics (Keohane et al 1984).…”
Section: Aetiologymentioning
confidence: 99%